Analysis of Civil Partnership of Notary Based on the Law of Notary Position - Tahir, Fonni (Tadulako Master Law Journal, 2018)
Analysis of Civil Partnership of Notary Based on the Law of Notary Position. The Law of Notary Position provides an opportunity for notaries to establish a Civil Partnership of notaries in the performance of their position. This is contrary to the notary profession, since the purpose of the formation of Civil Partnership is to seek the benefit to be distributed to allies as stipulated in the Civil Code. This study aimed to find out and comprehend (1) the formation of a civil partnership of notary in the implementation of the notary’s position: (2) the application of the principles of civil partnership stipulation in the Civil Code to civil partnership of notary. This research is a normative research that is a process to find out laws, legal principles, and legal doctrine to answer the legal problem. This study employed a statutory, comparison, and conceptual approaches. The results of this study indicate that: (1) the formation of civil partnership is not in line with the implementation of the notary position because the main purpose of the formation of civil partnership is to seek profit, while the obligation of the notary profession is to give priority to the society and the state. (2) the principles of civil partnership stipulation in the Civil Code differ from the principles of stipulation in the formation of notary civil partnerships, in the case of profit sharing. The form of civil partnership (Code Civil) applies profit sharing whereas in civil partnership of notary there is no profit sharing, but each notary receives honorarium in return for his services without any honorarium sharing. Therefore, a revision of the use of a civil partnership of notary term used in the Law of Notary Position is required.Keywords: civil partnership, notary, joint office, maatschap